Novel Cu(II)-based metal-organic framework STAM-1 as a sulfur host for Li-S batteries - Niščáková, V.; Almáši, Miroslav; Capková, Dominika; Kazda, Tomáš; Čech, Ondřej; Čudek, Pavel; Petruš, Ondrej; Volavka, D.; Orinaková, Renáta; Straková Fedorková, Andrea (NATURE PORTFOLIO, 2024)
Due to the increasing demand for energy storage devices, the development of high-energy density batteries is very necessary. Lithium-sulfur (Li-S) batteries have gained wide interest due to their particularly high-energy density. However, even this type of battery still needs to be improved. Novel Cu(II)-based metal-organic framework STAM-1 was synthesized and applied as a composite cathode material as a sulfur host in the lithium-sulfur battery with the aim of regulating the redox kinetics of sulfur cathodes. Prepared STAM-1 was characterized by infrared spectroscopy at ambient temperature and after in-situ heating, elemental analysis, X-ray photoelectron spectroscopy and textural properties by nitrogen and carbon dioxide adsorption at - 196 and 0 degrees C, respectively. Results of the SEM showed that crystals of STAM-1 created a flake-like structure, the surface was uniform and porous enough for electrolyte and sulfur infiltration. Subsequently, STAM-1 was used as a sulfur carrier in the cathode construction of a Li-S battery. The charge/discharge measurements of the novel S/STAM-1/Super P/PVDF cathode demonstrated the initial discharge capacity of 452 mAh g-1 at 0.5 C and after 100 cycles of 430 mAh g-1, with Coulombic efficiency of 97% during the whole cycling procedure at 0.5 C. It was confirmed that novel Cu-based STAM-1 flakes could accelerate the conversion of sulfur species in the cathode material.

Due to the increasing demand for energy storage devices, the development of high-energy density batteries is very necessary. Lithium-sulfur (Li-S) batteries have gained wide interest due to their particularly high-energy density. However, even this type of battery still needs to be improved. Novel Cu(II)-based metal-organic framework STAM-1 was synthesized and applied as a composite cathode material as a sulfur host in the lithium-sulfur battery with the aim of regulating the redox kinetics of sulfur cathodes. Prepared STAM-1 was characterized by infrared spectroscopy at ambient temperature and after in-situ heating, elemental analysis, X-ray photoelectron spectroscopy and textural properties by nitrogen and carbon dioxide adsorption at - 196 and 0 degrees C, respectively. Results of the SEM showed that crystals of STAM-1 created a flake-like structure, the surface was uniform and porous enough for electrolyte and sulfur infiltration. Subsequently, STAM-1 was used as a sulfur carrier in the cathode construction of a Li-S battery. The charge/discharge measurements of the novel S/STAM-1/Super P/PVDF cathode demonstrated the initial discharge capacity of 452 mAh g-1 at 0.5 C and after 100 cycles of 430 mAh g-1, with Coulombic efficiency of 97% during the whole cycling procedure at 0.5 C. It was confirmed that novel Cu-based STAM-1 flakes could accelerate the conversion of sulfur species in the cathode material.
Novel Cu(II)-based metal-organic framework STAM-1 as a sulfur host for Li-S batteries
Keywords: Lithium-sulfur battery; Cathode materials; Metal-organic framework; Energy storage; Lithium-sulfur battery; Cathode materials; Metal-organic framework; Energy storage